Economic efficiency evaluation, regional technological heterogeneity, and total factor productivity change in the industrial sector of China - Yan Ping; Wu Yingqin; Wu gang; Wasi Ul Hassan Shah (Humanities & Social Sciences Communications)
Abstract The sustainable growth of the industrial sector is one of the top economic goals of the Chinese government in recent decades. The central and provincial governments employed numerous economic policies to enhance economic efficiency and total factor productivity growth in the industrial sector of China. In response to the modern global challenges related to sustainable development, industrial sector transformation, and environmental and ecological issues, Chinese companies and governments have significantly improved their ecological and economic performance over the past two decades. Thus, the current paper determines the changes in the region’s economic efficiency, technology heterogeneity, and total factor productivity in China’s industrial sector from 2000 to 2022. This study utilizes the SBM-DEA model, Meta-technology analysis, and the Malmquist–Luenberger Index to assess the eco-efficiency, TGR, and TFPC in 31 mainland provinces and four regions of China. The study’s results demonstrate significant disparities in economic efficiency. The eco-efficiency of the industrial sector of China witnessed substantial growth from 2000 to 2012, followed by fluctuations after 2012. The average eco-efficacy (2000–2022) score was 0.7482, indicating a 25.18 percent improvement potential. The Meta frontier analysis reveals a significant technological level disparity across 4 different regions, and the Eastern region was found to have superior production technology with a TGR of 1. The Mean value of TFPC is 1.0423. This means that TFPC has grown at 4.23% during the study period. TFPC grows mainly due to technological change, as TC < EC. The results of the Kruskal-Wallis test indicate a statistically significant difference among the 4 regions of China.